2019
DOI: 10.1177/0892705719882998
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of organoclay dispersion into polystyrene-based nanocomposites by incorporation of SBS and maleic anhydride-grafted SBS

Abstract: In this study, organoclay-containing polystyrene (PS)-based nanocomposites were fabricated by extrusion in the presence of thermoplastic elastomer modifiers. Styrene–butadiene–styrene (SBS) rubber was used as the elastomeric compatibilizer and maleic anhydride (MA) was grafted onto SBS rubber at different ratios. Grafting was made via melt blending. Cloisite® 30B was used as the organoclay and it was added to PS and PS/SBS blends using a corotating twin-screw extruder, followed by injection molding. Clay loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…In another study, PS has been blended with 25% SBS and 1% SBS-g-MA and maximum 25% increase in impact resistance was achieved. 4 The PS polymer has been converted to polymer nanocomposites with different types of nanoparticles. 15,16 Halloysite nanotubes (HNTs) is a type of aluminosilicate clay with a hollow tubular geometry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, PS has been blended with 25% SBS and 1% SBS-g-MA and maximum 25% increase in impact resistance was achieved. 4 The PS polymer has been converted to polymer nanocomposites with different types of nanoparticles. 15,16 Halloysite nanotubes (HNTs) is a type of aluminosilicate clay with a hollow tubular geometry.…”
Section: Introductionmentioning
confidence: 99%
“…1 Melt compounding of PS with various types of thermoplastic elastomers has been done to overcome this disadvantage. 2 4 Rubber toughening by elastomeric inclusions in the polymer matrix is one of the most efficient methods of toughening utilized for rigid polymers. 5 –7 The high-impact PS known as a commercial polybutadiene rubber–toughened polymer has been widely used in industrial applications such as packaging, toys, bottles, housewares, household electronic appliances, containers, and light-duty industrial components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, additition of elastomeric compatibilizers 2210 and 8840 had little positive effect on the intercalation or exfoliation of silicate layers. The interaction between the functional groups of the elastomeric materials and hydroxyl groups on the clay surface may be weakened due to heat treatment or the decomposition of organic modifier, so that some portion of the ammonia salts may have exuded from the clay gallery, leading to a decrease in interlayer spacing [25,26]. Another reason of the collapse in basal spacing may be explained by the applied high pressure during the injection molding process [27].…”
Section: Resultsmentioning
confidence: 99%
“…The use of organoclay (Mag-CTA + ) has an impact on the morphology of the prepared nanocomposites, especially in the dispersion of in-situ polymerization methods. For these reasons, several nanocomposites based on polymers and organoclay were prepared [ 20 , 21 , 22 , 23 , 24 ]. By reviewing the literature, we found that no previously published work has described the use of natural clay as a nano-reinforcing filler in the preparation of green-nanocomposites based on rosin-limonene copolymer.…”
Section: Introductionmentioning
confidence: 99%